Hereditary tyrosinemia presenting as hepatocellular carcinoma in a young infant - Sivadas, Suchitra; Bhaskaran, Praveena; Panicker, Jayakuma Chandrasekhara; Chandrasekharan, Rajsekar; Bajad, Chandan; Ajith, Anjali (International Journal of Contemporary Pediatrics, 2021)
Hereditary tyrosinemia type 1 is an inborn error of metabolism that affects numerous organs, particularly liver, kidneys and peripheral nerves. It usually presents in infants less than six months of age with features of liver failure, hepatoblastoma or hepatocellular carcinoma. Diagnosis is by a combination of clinical, biochemical and imaging features. We report here the case of a four months old infant presenting with massive hepatosplenomegaly and coagulopathy. He was detected to have hepatocellular carcinoma secondary to tyrosinemia and initiated on treatment. This report highlights the importance of considering tyrosinemia in the differential diagnosis of infants presenting with hepatic disease. Early diagnosis is important due to the presence of effective treatment and for prenatal diagnosis in subsequent pregnancies.